2021
DOI: 10.1093/ajcn/nqaa337
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of lifestyle risk factors with overweight or obesity among adolescents: a multicountry analysis

Abstract: Background About 35% of the global burden of disease has roots in adolescence. Health in adolescence is an important determinant of health in adulthood. Objectives This study aimed to generate risk scores for lifestyle behaviors among adolescents and to estimate the country-specific prevalence of these risk scores. The study also examined the relations of lifestyle risk scores with overweight or obesity among adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Exercise and diet are particularly related to obesity (4). During the home confinement, students’ sleep was irregular, their indoor and sedentary activities increased, and their sport and outdoor activities decreased (19,26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise and diet are particularly related to obesity (4). During the home confinement, students’ sleep was irregular, their indoor and sedentary activities increased, and their sport and outdoor activities decreased (19,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive weight gain in early life is likely to lead to lifelong overweight and obesity and is associated with greater risk and earlier onset of chronic disorders, such as cardiovascular and metabolic diseases (2,3). In recent years, insufficient outdoor physical activity has been recognized as a major risk factor for pediatric overweight or obesity development (4). A large and growing evidence base also suggested that unhealthy weight gain of children mainly occurred during summer months, when they were out of school (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study, with data from 851 Colombian adolescents, a positive association was found between low physical activity levels and high insulin resistance in the obesity status of adolescents [ 20 ]. In addition, the evidence shows that during adolescence adolescents change their behavior significantly, adopting an unhealthy lifestyle, including the use of technology, poor nutritional diet, and low physical activity, which increase the risk of overweight and obesity; shows the importance of monitoring these variables and other health-related variables during adolescence [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient outdoor physical activity has been suggested as a major risk factor for overweight pediatric or obesity development. 29 It also provided that excessive weight gain in children mainly occurred during the summer, while they were not going to school. 30 …”
Section: Discussionmentioning
confidence: 99%